2018
DOI: 10.1016/j.ijbiomac.2018.02.152
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharides from Phormidium versicolor (NCC466) protecting HepG2 human hepatocellular carcinoma cells and rat liver tissues from cadmium toxicity: Evidence from in vitro and in vivo tests

Abstract: The in vitro antioxidant, cytotoxic and cytoprotective properties and in vivo hepatoprotective activities of crude polysaccharides extracted from cyanobacteria Phormidim versicolor NCC466 (CFv-PS) were investigated. The CFv-PS, identified as heteropolysaccharides with molecular weight of 63.79kDa, exhibited relatively strong antioxidant activity, in a concentration-depended manner, in vitro assays. Additionally, CFv-PS did not induce cytotoxic effect on HepG2 human hepatocellular carcinoma cells within the ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…ETS05 showed that the main sugar residues composing the polymer were xylose, rhamnose, and glucose, the sum of the three giving 64% of the total composition, while galactose, fucose, mannose, arabinose, glucosamine, and two uronic acids were present in minor amounts. A total of 10 detectable monosaccharides were identified here, which is comparable to species of the genus Phormidium such as the eight-to-twelve monosaccharides in P. tenue [54,55] or the ten in P. versicolor [22]. Cyanobacterial polysaccharides showing anti-inflammatory activity on various animal models, as the capsular polysaccharides from Mastigocladus laminosus [56,57] or sacran from Aphanothece sacrum [20,58], are composed of various proportions of eight main sugars, namely glucose, galactose, mannose, xylose, rhamnose, fucose, and galacturonic and glucuronic acids.…”
Section: Discussionmentioning
confidence: 76%
“…ETS05 showed that the main sugar residues composing the polymer were xylose, rhamnose, and glucose, the sum of the three giving 64% of the total composition, while galactose, fucose, mannose, arabinose, glucosamine, and two uronic acids were present in minor amounts. A total of 10 detectable monosaccharides were identified here, which is comparable to species of the genus Phormidium such as the eight-to-twelve monosaccharides in P. tenue [54,55] or the ten in P. versicolor [22]. Cyanobacterial polysaccharides showing anti-inflammatory activity on various animal models, as the capsular polysaccharides from Mastigocladus laminosus [56,57] or sacran from Aphanothece sacrum [20,58], are composed of various proportions of eight main sugars, namely glucose, galactose, mannose, xylose, rhamnose, fucose, and galacturonic and glucuronic acids.…”
Section: Discussionmentioning
confidence: 76%
“…3,4 Long-term exposure to cadmium causes tissue damages in various organs, especially in livers and kidneys. 5 Cadmium in liver cells usually induces production of metallothionein (MT), 6,7 which could bind cadmium and transfer it to kidneys. Most of the MT-cadmium complex is reabsorbed and deposited in the renal proximal convoluted tubules, and leads to irreversible damage to the structure and function of the kidney eventually.…”
Section: Introductionmentioning
confidence: 99%
“…Through food chain transfer, cadmium ultimately enters human bodies and has a long biological half‐life about 10 to 30 years 3,4 . Long‐term exposure to cadmium causes tissue damages in various organs, especially in livers and kidneys 5 . Cadmium in liver cells usually induces production of metallothionein (MT), 6,7 which could bind cadmium and transfer it to kidneys.…”
Section: Introductionmentioning
confidence: 99%
“…G. resinaceum polysaccharide-rich fractions exhibited weak cytotoxic effects against MDA-MB 231, Hela, and HepG 2 with CC 50 range of 298–420 µ g/mL after 48 h of incubation. Polysaccharides are generally known for their in vitro anticancer activities either by regulating cell cycle, intracellular Ca 2+ concentration triggering apoptosis, immunopotentiation, or miR-125b inhibiting T regs accumulation and function [ 41 46 ]. These properties might be associated with the specific conformation of polysaccharides and their affinity for cancer cell surface [ 47 ].…”
Section: Discussionmentioning
confidence: 99%